Pola Adopsi Teknologi Secara Parsial pada Pelaku UMKM di Kota Tuban dalam Kegiatan Pemasaran - Nur Hidayatul Istiqomah; Agus Hermawan; Wening Patmi Rahayu (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The digitalization of MSMEs has become a central agenda in national economic development; however, realities on the ground reveal a significant gap between policy expectations and the actual practices of business actors. This study aims to understand patterns of technology use, explore MSME actors’ perceptions of technology, and identify factors that hinder optimal technology adoption. Using a qualitative approach with a case study method involving two MSME actors in Tuban City, data were collected through in-depth interviews, direct observation, and documentation. The findings reveal three main points: first, technology is used situationally only when orders come in via WhatsApp rather than as part of a planned business strategy; second, MSME actors perceive technology as complex and not particularly important for the sustainability of their businesses; third, low levels of digital literacy reinforce the tendency to maintain conventional business practices. This study introduces the concept of partial technology adoption as a novel conceptual contribution, describing a condition in which business actors do not entirely reject technology, yet do not strategically integrate it into their business operations. The implications of this research are relevant for policymakers designing MSME digitalization programs and for practitioners involved in business development assistance